Soil microbial activity and hairy beggarticks’ germination after application of crude glycerin - Caixeta, Matheus Ramos; Carvalho, Saul Jorge Pinto de; Colpa, Poliana Coste e; Andrade, Márcio Donizetti de; Santos, Breno Régis (Revista Ceres, 2017)
Biodiesel stands out as an alternative for petroleum-based products, but its production generates a large amount of by-products. This study was carried out at the Instituto Federal de Educação, Ciência e Tecnologia do Sul de Minas Gerais, Campus Machado, with the objective of evaluating the impacts of the disposal of crude glycerin on agricultural soil and its microbial activity as well as in plant development. An experiment with a completely randomized design, five treatments, and five replicates was developed in the laboratory to analyze microbial activity. Soil samples of 100 g were incubated for 36 days with concentrations of crude glycerin, namely: 0; 48.7; 146.1; 292.2 L ha-1. Besides these four treatments, flasks without soil and glycerin have composed one more treatment. During this period, the CO2 volume released in each sample was evaluated 11 times. Another experiment was developed in the laboratory with hairy beggarticks’ achenes to evaluate crude glycerin effects on plant development. A randomized complete block design was used in a 4x2 factorial scheme, with five replicates, the same glycerin concentrations, and two glycerin sources (laboratory and biodiesel plant-unit). Crude glycerin stimulated soil microbial activity for doses of up to 143.83 L ha-1, being a positive indicative for future studies on its application to agricultural soils. Glycerin applications reduced the hairy beggarticks’ root protrusion, even at the lowest doses. Residues have Na+ contents that limit their application in agricultural soils.